The Economic and Politic Relations Between Bulgaria and Germany. A Short Historical Perspective - Sebastian-Florian Enea; Irina-Elena Gentimir (CES Working Papers, 2012)
Members of the European Union, Germany and Bulgaria are united by the same values and expectations. Both countries aim to closer relations in order to insure economic growth and a high competitiveness level. The objective of this article is to present, from a historical approach, the evolution of the economic and political relations between Bulgaria and Germany. The methodological process adopted in the present analyses is of both qualitative and quantitative nature. The article uses data from theoretical and empirical research on the economic and politic relations between Germany and Bulgaria and presents them from a historical perspective. Even though they were hit by the economic crisis, the two member states of the EU continued to maintain their economic relation on a positive trend. The recovering German economy continues to help Bulgaria, which has a hard time coming out of the crisis. The good economic relationship between the two partners will continue to be successful, the trade and investment flows being expected to double until 2015.
Keywords: F14; F59; 330; Germany; Bulgaria; economic relations; trade flows; foreign direct investments Romania